If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 5x = 180 Solving 15 + 5x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5x = 180 + -15 Combine like terms: 15 + -15 = 0 0 + 5x = 180 + -15 5x = 180 + -15 Combine like terms: 180 + -15 = 165 5x = 165 Divide each side by '5'. x = 33 Simplifying x = 33
| (y+4)-3y=1+y | | 60+(k+l)=k*2 | | 3(3+2b)=-2(5-4b) | | 2m=2m+12 | | y=x^2+12x+32are-4and-8 | | 45z^3+20z^2+9z+4= | | 6(u-7)-8u=-34 | | ax^2-12x-3=6 | | -3(2-9)-a=1 | | 5x-2=-21 | | 25-5x+x=18+3x | | 11b^3-6b^2+11b-6= | | 6(2x-6)-4(x+1)-16x= | | 4=6-2x+1 | | -0006=.02x | | 10x+4=30 | | -15h^3+-6h^4+30h^5= | | 5x+3=0.57 | | .35=1.5 | | 16b^2-48b+11=0 | | a=3(3b+4c) | | -53=9x | | 4+13n-2=8n+29-4n | | 3y-2=8-2y | | -81=-(1-7k)+3k | | H=-16t^2+32t+20 | | x^3-4x^2-16x+15=0 | | 4x-16=6x+20 | | 0.1(x+40)+.1=5 | | 3t^4-6t^3-9t+12= | | 2x^2-3x^2-18x+27=0 | | (5x^2+2x+1)-(3x^2-4x-2)= |